2017
DOI: 10.18632/oncotarget.19781
|View full text |Cite
|
Sign up to set email alerts
|

The impact of post-radioiodine therapy SPECT/CT on early risk stratification in differentiated thyroid cancer; a bi-institutional study

Abstract: ObjectiveSPECT/CT has numerous advantages over planar and traditional SPECT images. The aim of this study was to evaluate the role of post-radioiodine therapy SPECT/CT of patients with differentiated thyroid cancer (DTC) in early risk classification and in prediction of late prognosis.Patients and methods323 consecutive patients were investigated after their first radioiodine treatment (1100–3700 MBq). Both whole body scan and SPECT/CT images of the head, neck, chest and abdomen regions were taken 4–6 days aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The favorable results of SPECT/CT and the incremental benefit over WBS obtained in this study agree with the data reported in previous studies in both pre [3,38,39] and post [40][41][42][43][44][45]56,57] ablation phases as well as during long-term follow-up [9,10,[46][47][48][49][50], including in the latter cases data obtained with routine use of the procedure [9,10,47].…”
Section: Discussionsupporting
confidence: 92%
“…The favorable results of SPECT/CT and the incremental benefit over WBS obtained in this study agree with the data reported in previous studies in both pre [3,38,39] and post [40][41][42][43][44][45]56,57] ablation phases as well as during long-term follow-up [9,10,[46][47][48][49][50], including in the latter cases data obtained with routine use of the procedure [9,10,47].…”
Section: Discussionsupporting
confidence: 92%
“…The current findings are similar to other studies where risk classification was changed in 6.4%, 25% and 35.6% of patients, respectively, after SPECT/CT and change in TNM stage was seen in 6.1%, 25.9% and 21% of patients. 2 , 3 , 16 , 20 , 26 Similarly, change in therapeutic plan was observed in 2.0%, 24% and 19.4% of patients after SPECT/CT. 3 , 7 , 19 This variability in results may be explained due to differences in the qualitative assessment of image findings, patient population, age, histopathologies and variation in study protocols.…”
Section: Discussionmentioning
confidence: 95%
“…In a bi-institutional study, if compared to planar PT-WBI, PT-SPECT/CT WBI altered patients' risk category in 35.6% of cases, which consequently changed the patient management and follow-up [61].…”
Section: Post-treatment Whole-body Imagingmentioning
confidence: 99%